Boron‐Doped, Carbon‐Coated SnO2/Graphene Nanosheets for Enhanced Lithium Storage. Issue 14 (18th February 2015) - Liu, Yuxin; Liu, Ping; Wu, Dongqing; Huang, Yanshan; Tang, Yanping; Su, Yuezeng; Zhang, Fan; Feng, Xinliang
Abstract Heteroatom doping is an effective method to adjust the electrochemical behavior of carbonaceous materials. In this work, boron‐doped, carbon‐coated SnO2/graphene hybrids (BCTGs) were fabricated by hydrothermal carbonization of sucrose in the presence of SnO2/graphene nanosheets and phenylboronic acid or boric acid as dopant source and subsequent thermal treatment. Owing to their unique 2D core–shell architecture and B‐doped carbon shells, BCTGs have enhanced conductivity and extra active sites for lithium storage. With phenylboronic acid as B source, the resulting hybrid shows outstanding electrochemical performance as the anode in lithium‐ion batteries with a highly stable capacity of 1165 mA h g−1 at 0.1 A g−1 after 360 cycles and an excellent rate capability of 600 mA h g−1 at 3.2 A g−1, and thus outperforms most of the previously reported SnO2‐based anode materials.